1994
DOI: 10.1021/j100100a007
|View full text |Cite
|
Sign up to set email alerts
|

1La-1Lb Coupling in the Excited State of 3-Methylindole and Its Polar Clusters

Abstract: The excited state dynamics of 3-methylindole are investigated with the goal of further characterizing the nonadiabatic interaction giving rise to ' La-%, mixing in its excited singlet state. Both the bare molecule and its clusters with polar species display evidence of coupling between these two close-lying states. By using a series of successively more polar ligands, it is shown that the strength of the interaction between the ' Lb and 'La states can be "tuned", permitting the observation of progressive chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 4 publications
3
55
0
Order By: Relevance
“…12 Their quoted frequency of 614 cm -1 falls between peaks at 611 and 619 cm -1 , both of which we and Sammeth et al find to have 1 L a character. However, the 718 cm -1 peak was found to be 1 L b by Sammeth et al, and we found a corresponding L b peak in the complex spectra.…”
Section: -Misupporting
confidence: 53%
See 2 more Smart Citations
“…12 Their quoted frequency of 614 cm -1 falls between peaks at 611 and 619 cm -1 , both of which we and Sammeth et al find to have 1 L a character. However, the 718 cm -1 peak was found to be 1 L b by Sammeth et al, and we found a corresponding L b peak in the complex spectra.…”
Section: -Misupporting
confidence: 53%
“…Our findings are consistent with an amended Wallace group hypothesis concerning the 1 L a radiationless channel. 12 They propose that N-H dissociation occurs through coupling to levels of another state, a triplet or high-energy dissociative levels of the ground state. Another possibility not ruled out by our results is excited state tautomerization.…”
Section: -Methoxyindole (5-moi)mentioning
confidence: 99%
See 1 more Smart Citation
“…( 1 L a state), see also Figure 2. For aromatic molecular systems such as indoles, [27][28][29][30][31][32][33] tryptophane, [34] or pyrene derivatives [35] internal conversion between these 1 L b and 1 L a levels has been suggested in the interpretations. For 1-naphthol [36,37] the 1 L b !…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, the combination of the present and previous results can help to clarify the models reported in the bibliography for the explanation of the anomalous large Stokes shift and fluorescence quenching of indole in polar solvents. Most of these models highlight the crucial role played by the solvent on the relative stabilisation and relaxation of the two close low-lying excited states 1 L a and 1 L b of the indole chromophore [27][28][29]. In gas phase, the 1 L b state lies below the 1 L a state by about 1400 cm À1 [30].…”
Section: Steady-state and Time-resolved Fluorescence Measurementsmentioning
confidence: 99%